(3EjVGM GdGTJHGg aj CSeGA GdQhGIs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hEjVGMgG Ydi hLg GdEjLGR hGdGNJUGQ HGSJbUGA CMhGd GdQLGd (B... (3CHh QGaY, GSeg CSde(B...s
(3BNQgG (B:s
(3ahLOJ CHG LYaQ bO eGJ(B. (3CHh GdMSjf GdYbQGfj, HGdbGa hGdfhf HYO GdCda bHd GdjGA(B. (3agPG BNQ eG CQOfG EKHGJg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3GdCYdGe(B: (3L(B2(3, (B228s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs